2011
DOI: 10.1021/jp112174s
|View full text |Cite
|
Sign up to set email alerts
|

UV Resonance Raman Finds Peptide Bond−Arg Side Chain Electronic Interactions

Abstract: We measured the UV resonance Raman excitation profiles and Raman depolarization ratios of the arginine (Arg) vibrations of the amino acid monomer, as well as, Arg in the 21-residue predominantly alanine peptide, AAAAA(AAARA)3A (AP) between 194 and 218 nm. Excitation within the π→π* peptide bond electronic transitions result in UVRR spectra dominated by amide peptide bond vibrations. The Raman cross sections and excitation profiles indicate that the Arg side chain electronic transitions mix with the AP peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…A positive broad peak around 195-200 nm along with a negative peak at 226-229 nm indicate the presence of a β-sheet like arrangement. The red-shifted β-sheet signal has been previously observed and it has been shown to π* transitions of the peptide bonds [39,40] and the carboxylic acid moieties in the peptide [41,42]. The absorption peak at 280 nm is attributed to the aromatic side chains of Trp, with a less intense π The light-absorption properties of the pentapeptide hydrogel were in recording its UV-Vis spectrum in aqueous medium (Figure 8A).…”
Section: Optical Properties Structural Conformation and Crystallinity...mentioning
confidence: 73%
See 1 more Smart Citation
“…A positive broad peak around 195-200 nm along with a negative peak at 226-229 nm indicate the presence of a β-sheet like arrangement. The red-shifted β-sheet signal has been previously observed and it has been shown to π* transitions of the peptide bonds [39,40] and the carboxylic acid moieties in the peptide [41,42]. The absorption peak at 280 nm is attributed to the aromatic side chains of Trp, with a less intense π The light-absorption properties of the pentapeptide hydrogel were in recording its UV-Vis spectrum in aqueous medium (Figure 8A).…”
Section: Optical Properties Structural Conformation and Crystallinity...mentioning
confidence: 73%
“…The most characteristic absorption features of the pentapeptide were observed in the far-UV (<220 nm) and the near-UV regions (280 nm). In particular, the strong absorption peak observed below 220 nm is attributed to the π↔π* transitions of the peptide bonds [39,40] and the carboxylic acid moieties in the peptide [41,42]. The absorption peak at 280 nm is attributed to the aromatic side chains of Trp, with a less intense π↔π* transition identified as a shoulder at 292 nm.…”
Section: Optical Properties Structural Conformation and Crystallinity...mentioning
confidence: 99%
“…Recently, we studied the excitation profiles of arg and found that the overtone of the CN 3 out-of-plane vibration is enhanced as the excitation wavelength is tuned into resonance. 30 …”
Section: Resultsmentioning
confidence: 99%
“…3A). 25,26 The structure of the wild-type EGFR kinase domain has been previously determined in both active and inactive conformations. 27,28 The L858R mutation lies in the N-terminal portion of the activation loop.…”
Section: Raman and Ihc Analyses Of Egfr Status In Nsclc Patientsmentioning
confidence: 99%